Confirmed disability progression as a marker of permanent disability in multiple sclerosis. (9th June 2022) - Sharmin, Sifat; Bovis, Francesca; Malpas, Charles; Horakova, Dana; Havrdova, Eva Kubala; Izquierdo, Guillermo; Eichau, Sara; Trojano, Maria; Prat, Alexandre; Girard, Marc; Duquette, Pierre; Onofrj, Marco; et al.
Abstract: Background and purpose: The prevention of disability over the long term is the main treatment goal in multiple sclerosis (MS); however, randomized clinical trials evaluate only short‐term treatment effects on disability. This study aimed to define criteria for 6‐month confirmed disability progression events of MS with a high probability of resulting in sustained long‐term disability worsening. Methods: In total, 14, 802 6‐month confirmed disability progression events were identified in 8741 patients from the global MSBase registry. For each 6‐month confirmed progression event (13, 321 in the development and 1481 in the validation cohort), a sustained progression score was calculated based on the demographic and clinical characteristics at the time of progression that were predictive of long‐term disability worsening. The score was externally validated in the Cladribine Tablets Treating Multiple Sclerosis Orally (CLARITY) trial. Results: The score was based on age, sex, MS phenotype, relapse activity, disability score and its change from baseline, number of affected functional system domains and worsening in six of the domains. In the internal validation cohort, a 61% lower chance of improvement was estimated with each unit increase in the score (hazard ratio 0.39, 95% confidence interval 0.29–0.52; discriminatory index 0.89). The proportions of progression events sustained at 5 years stratified by the score were 1: 72%; 2: 88%; 3: 94%; 4: 100%. The results of the CLARITY trial were confirmed for reduction of disability progression that was >88% likely to be sustained (events with score ˃1.5). Conclusions: Clinicodemographic characteristics of 6‐month confirmed disability progression events identify those at high risk of sustained long‐term disability. This knowledge will allow future trials to better assess the effect of therapy on long‐term disability accrual. Abstract : Using 13, 321 confirmed disability progression events from the MSBase registry, a sustained progression score was developed based on patients' characteristics at the time of progression. The sustained progression score helps identify those confirmed progression events that will be sustained over at least 5 years. This score allows randomized trials to establish the effect of therapy not only on short‐term but also on long‐term disability accrual, as demonstrated in our reanalysis of the Cladribine Tablets Treating Multiple Sclerosis Orally (CLARITY) trial data.